2022
DOI: 10.1039/d1tb02787e
|View full text |Cite
|
Sign up to set email alerts
|

Targeted killing of tumor cells based on isoelectric point suitable nanoceria-rod with high oxygen vacancies

Abstract: Nanozymes have great potential application in tumor treatment because of their good stability, high biocompatibility, easy preparation and versatility. However, it remains a challenge to design of highly active nanozyme...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
1
14
0
Order By: Relevance
“…It is necessary to improve the enzyme-like activities of nanoceria further to enable practical treatments. Most previous studies were focused on the morphology or doping to enhance the catalytic activity of nanoceria. , We also found that nanoceria-rods with high enzymatic activity had more powerful tumor-killing capability compared than nanoceria-polyhedra and cubes …”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…It is necessary to improve the enzyme-like activities of nanoceria further to enable practical treatments. Most previous studies were focused on the morphology or doping to enhance the catalytic activity of nanoceria. , We also found that nanoceria-rods with high enzymatic activity had more powerful tumor-killing capability compared than nanoceria-polyhedra and cubes …”
Section: Introductionsupporting
confidence: 71%
“…The oxygen vacancies of the Pt/CeO 2 -NR and Pt/CeO 2 -R nanozymes were characterized by Raman spectroscopy. The intensity ratio for the peaks at 595 cm –1 (IVo) and approximately 465 cm –1 (IF2g) were used to quantify the surface concentration of oxygen vacancies. , As Figure a shows, the single-atom Pt/CeO 2 -NR and CeO 2 -NR carriers had lower oxygen vacancy concentrations (IVo/IF2g, Pt/CeO 2 -NR 0.054 compared with CeO 2 -NR 0.012). After H 2 reduction at 600 °C, the oxygen vacancy concentrations of Pt/CeO 2 -R and CeO 2 -R were increased (Ivo/IF2g, Pt/CeO 2 -R 0.114 compared with CeO 2 -R 0.023) (Figure b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 174,176 ] The principle of crystal defects indicates that the local bonding and electronic properties of matrix metals may be changed by site‐specific defect engineering by the doping of different metal ions, thereby enhancing the recognition and response to different pH conditions (Figure 10b). [ 174,190,191 ] CeO 2 NPs had low POD‐like activity until pH gradually dropped below 5, [ 192 ] while Fe 2+ ‐doped CeO 2 nanozymes changed their valence state more sensitively. In particular, Fe 2+ ‐doped CeO 2 converted to Ce 3+ when pH = 6.5 to exert POD‐like activity and produce ROS, while it could also change to Ce 4+ when pH = 7.4 to affect CAT‐like activity, thus removing ROS and reducing oxidative stress in inflamed tissues.…”
Section: Optimization Strategy For the Efficacy Of Mnmsmentioning
confidence: 99%
“…Nanozymes with multiple enzymatic activities can effectively produce reactive oxygen species in the tumor microenvironment through cascade catalytic reactions, thereby promoting the apoptosis of cancer cells (Zhao et al, 2021b;Yao et al, 2022b;Wang et al, 2022f). Ma et al (2022) designed nanozymes with three nanoceria structures including nanoceria-cube, nanoceria-poly and nanoceria-rod. Among them, nanoceria-rod with highest concentration of surface oxygen vacancies has the highest POD-like and OXD-like enzyme activity.…”
Section: Apoptosis Inductionmentioning
confidence: 99%